4CPS-046 A qualitative study of feasibility and acceptability of a pharmacy prioritisation toolkit by a frailty focused multidisciplinary team in an acute hospital emergency department. Issue 1 (23rd March 2023) - Kennedy, E; Silvari, V
Abstract : Background and Importance: The number of frail, older patients presenting to the emergency department (ED) is increasing. As frailty is highly linked to medication issues, a pharmacy prioritisation toolkit (PPT), completed by a frailty multidisciplinary team (MDT), is effective to identify patients who would benefit the most from the frailty pharmacist's medication review. Aim and Objectives: To investigate feasibility and acceptability of a five-question PPT by the MDT after four months of use. Material and Methods: An anonymised, mixed methods questionnaire (open/closed questions) was distributed to the MDT (consultant, registrar and clinical nurse in geriatrics, dietician, occupational, physio and speech & language therapists).The questions aimed at establishing barriers and facilitators to the PPT. The straightforwardness of the toolkit questions was ranked using a Likert scale. A focus group was held to expand on the results of the questionnaire and inform future work to enhance the toolkit use. Results: Of 8 questionnaires circulated, 7 were returned. Barriers identified, in order most mentioned theme to least: · difficulty identifying high risk medications · lack of full medical/medication history in ED · difficulty interpreting handwritten notes · time taken to complete the toolkit Although time taken to complete the PPT was a barrier, 5 respondents reported an average of 4 minutes for completion, which was deemed acceptable when discussing at the focus group. The group agreed, that some barriers are not modifiable such lack of full medical/medication history in ED. The most common facilitator was recognition that the tool clearly identifies when a pharmacy review is needed. Further education, self-learning and practice of the tool, but also upskilling on high risk medications and falls related medications, were considered potential future facilitators. 'Regular use of more than 10 medications' was the most straightforward question to answer in the toolkit while the least was 'Reason for admission potentially related to medications or admitted with non-mechanical fall'. Conclusion and Relevance: The toolkit was generally accepted by the MDT, the concise completion time was considered adequate taking into account the high prevalence of medication issues in frail patients. Based on the responses, further education to the frailty MDT is planned, with main focus on recognition of high risk medications and falls related medications. References and/or Acknowledgements: Conflict of Interest: No conflict of interest